Peningkatan Menulis Huruf Hijaiyah untuk ANak untuk Anak Usia 2-6 Tahun Melalui Media Papan Pasir Di TPQ Al-Kautsar - Ma'isyatul Ais Aisiyah (Universitas Muhammadiyah Gresik, 2022)
Ma’isyatul Aisiyah. 2021. Improvement of writing hijaiyah letters for children aged 2 – 6 years through the sandboard at TPQ AL – KAUTSAR.Skripsi, Early Childhood Islamic Education Study Program, Islamic Religion Faculty, Muhammadiyah University Gresik. Mentor :Ajeng Rizki Safira, M.Pd, Fitri Ayu Fatmawati, M.Pd. In learning, there are still many students who are in the PRA TK volume, volume 1, volume 2 who lack insight and are motivated about writing hijaiyah letters, making these children lazy to learn. In this research on board media, it is useful to increase insight into writing hijaiyah letters in early childhood, so that children understand more about writing hijaiyah letters. The function of the media, among others, is to help the learning process, make it easier for students to accept the subject matter given by the teacher. In this study using quantitative research methods.research design pre-experimental design with one-group prestest-posttest design. The statistics used are comparative and non-parametric statistics, meaning that the statistics are used to analyze data by describing or describing the data that has been collected as it is without intending to make conclusions that apply to the general public or generalization. TK PRA volume, Volume 1, Volume 2.0 – 6 years old. The results of research on learning to improve writing hijaiyah letters for children aged 2-6 years through sandboards at TPQ AL - Kautsar show that the learning process is greatly improved because children in the PRA TK volume, volume 1, volume 2, already understand and understand the insight about the difference between writing letters and writing letters. percentage 34% Because learning to improve writing hijaiyah letters for children aged 2-6 years through the sandboard at TPQ AL – Kautsar shows that the learning process is greatly improved because the children of PRA TK, volume 1, volume 2 are said to be effective. Keyword : Ma’isyatul Aisiyah. 2021. Improvement of writing hijaiyah letters for children aged 2 – 6 years through the sandboard at TPQ AL – KAUTSAR.Skripsi, Early Childhood Islamic Education Study Program, Islamic Religion Faculty, Muhammadiyah University Gresik. Mentor :Ajeng Rizki Safira, M.Pd, Fitri Ayu Fatmawati, M.Pd. In learning, there are still many students who are in the PRA TK volume, volume 1, volume 2 who lack insight and are motivated about writing hijaiyah letters, making these children lazy to learn. In this research on board media, it is useful to increase insight into writing hijaiyah letters in early childhood, so that children understand more about writing hijaiyah letters. The function of the media, among others, is to help the learning process, make it easier for students to accept the subject matter given by the teacher. In this study using quantitative research methods.research design pre-experimental design with one-group prestest-posttest design. The statistics used are comparative and non-parametric statistics, meaning that the statistics are used to analyze data by describing or describing the data that has been collected as it is without intending to make conclusions that apply to the general public or generalization. TK PRA volume, Volume 1, Volume 2.0 – 6 years old. The results of research on learning to improve writing hijaiyah letters for children aged 2-6 years through sandboards at TPQ AL - Kautsar show that the learning process is greatly improved because children in the PRA TK volume, volume 1, volume 2, already understand and understand the insight about the difference between writing letters and writing letters. percentage 34% Because learning to improve writing hijaiyah letters for children aged 2-6 years through the sandboard at TPQ AL – Kautsar shows that the learning process is greatly improved because the children of PRA TK, volume 1, volume 2 are said to be effective. Keyword :Sandboard Media, Hijaiyah Letters